Experimental and numerical study of the flexural behaviour of ultra-high performance fibre reinforced concrete beams. (1st May 2017) - Singh, M.; Sheikh, A.H.; Mohamed Ali, M.S.; Visintin, P.; Griffith, M.C.
Highlights: UHPFRC mix with conventional aggregates is used to manufacture beams. Stress-strain behaviour of UHPFRC under compression and tension is presented. Flexural behaviour of large-scale UHPFRC beams is presented. Finite element analysis of beams is conducted using concrete damaged plasticity model. Abstract: The development of standard analytical procedures and design guidelines for concrete requires extensive tests at material and structural level. For ultra-high performance fibre reinforced concrete (UHPFRC) this task is even more complicated than that of conventional concrete due to the potential range of fibre types and volume fractions. The experimental task of large scale structural members to develop the design procedures can be reduced by adopting an alternative way in which the concrete material model available in finite element packages are validated with the limited number of tests conducted on material and structural members. The validated numerical models can further used to study the effect on the structural behaviour due to change in geometry, loading conditions and reinforcement. Therefore the objective of the present study is to investigate the efficacy of the hybrid approach of validating the existing concrete model to study the behaviour of large-scale structural members made up of UHPFRC. For this four full-scale beams with varied spans and cross-sections were fabricated with the indigenously developed UHPFRC using conventional materials and mixing methods and tested under different loading conditions until failure. Numerical models were developed and validated with the test results of the beams for which the concrete damaged plasticity (CDP) model was adopted to characterize the behaviour of UHPFRC material. The material parameters required to define the constitutive model were identified by conducting direct/uniaxial tension and compression tests. The results obtained from the numerical models shows that the CDP model can accurately predict the load/moment carrying capacities of the UHPFRC beams. The results also show a good capability of the numerical models to predict the overall load deflection behaviour of the UHPFRC beams.